Bank lending and its impact on economic performance (a case study of Czechia) - Azbekov, Omirbek (2022)
Banks are playing crucial role in world economy. Several studies have shown how lending is connected to economic development of the country in the emerging markets. In the study, the connection of loans given by banks on economic growth in Czech Republic will be researched. In this research, there will be quantitative analysis applied mainly considering multiple regression and ARIMA model analysis with the main data about loans coming from Czech National Bank and check not only the effect of lending but also take in consideration the branches and sectors they are related to. Moreover, there will be an attempt to provide forecast for the loans using ARIMA and based on those values make a forecast for those economic indicators.